Facile Synthesis of 2-Amino-4-alkoxypyrimidines via Consecutive Nucleophilic Aromatic Substitution (SNAr) Reactions - Kim, Juhyeon; Cho, Yong Seo; Min, Sun-Joon (WILEY-V C H VERLAG GMBH, 2016)
A transition-metal-free and regioselective synthesis of a series of 2-amino-4-alkoxypyrimidines is described. The SNAr alkoxylation of 2,4-dichloropyrimidines regioselectively provided 2-chloro-4-alkoxypyrimidines, which were subsequently subject to the second SNAr amination with cyclic amines in the presence of triethylamine at high temperature to afford 2-amino-4-alkoxypyrimidines in good overall yield.
Keywords: CROSS-COUPLING REACTIONS; REGIOSELECTIVE 4-AMINO-DE-CHLORINATION; HETEROCYCLES; PYRIMIDINES; INHIBITOR; EFFICIENT